Characterization And Flammability Of Ethylene Vinyl Acetate (Eva)/Zeolite Composites - Nguyen, Van Thuong (2014)

(untitled)
This thesis describes the fabrication, characterization and properties of natural zeolite as filler in ethylene vinyl acetate (EVA) composites. One of the main objectives of this research is to determine the effect of zeolite loading on properties of EVA matrix composites. EVA composites at different loading of zeolite (5-25 vol. %) were prepared using Thermo Haake Polydrive internal mixer and were then compression molded according to standard test specimen. Tensile test and dynamic mechanical analysis (DMA) were performed to characterize the mechanical properties of EVA/zeolite composites. The tensile test can also be explained from the analysis of Scanning Electron Microscopy (SEM) micrograph of the tensile fractured surfaces. Besides, the influences of surface modifications on the properties of EVA/zeolite composites were also investigated. The interfacial interactions between EVA and zeolite were modified by crosslinking of EVA with dicumyl peroxide (DCP); cation exchange method using organic surfactant (octadecylamine) and also silane treatment using 3-aminopropyltriethoxysilane (AMPTES). In addition, Fourier Transform Infra red (FTIR) spectra analyses were performed in order to study the interaction between the composites and functional group of the surface modifiers. The application of surface modifications was proved to enhance the mechanical and morphological properties of EVA/zeolite composites. Thermal properties of the composites were also characterized by means of thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Intumescent flame retardant system consisting of ammonium polyphosphate (APP)/ pentaerythritol (PER) was used to enhance the thermal properties and fire retardancy of EVA/zeolite composites. The mechanical properties examined by tensile test indicated that the introduction of both flame retardants lead to deterioration of tensile strength and elongation at break of EVA/zeolite composites. However, the tensile modulus of the composites was significantly enhanced attributed to the rigidity of APP particles. The results of DSC and TGA showed that both types of flame retardants have the ability to enhance the thermal stability of EVA/zeolite composites. Meanwhile the results of vertical burning testing (UL-94-V) and limiting oxygen index (LOI) measurement revealed that the flame retardants could also reduce the flammability of the composites by achieving V-0 UL94-v rating and increased LOI value, respectively.